PENGARUH E-SERVICE QUALITY PADA ONLINE TRAVEL AGENT TERHADAP ELECTRONIC WORD OF MOUTH PELANGGAN PADA MASA COVID-19 - Viccy Putialyunissa, - (2022)
The dissemination of information in the form of Electronic Word of Mouth (EWOM) provided by customers regarding travel experiences during the Covid-19 pandemic is an effort to maintain its existence, so EWOM is an urgency in this study. The purpose of this study was to obtain an overview and influence of E-Service Quality on Electronic Word of Mouth. The type of research used is descriptive verification by describing and describing the variables studied and then obtaining conclusions. The dependent variable in this study is EWOM and the independent variable Eservice quality. The population in this study are OTA customers in Indonesia during the Covid-19 period. Sampling in this study using simple random sampling using probability sampling techniques of 200 respondents. The analysis technique used is Structural Equation Modeling (SEM) using the IBM SPSS AMOS for Windows program tool. The findings in this study found that the description of E-service quality and EWOM was in the high category. The research that has been conducted also suggests that E-service quality has a positive and significant influence on EWOM; the ease of use dimension in E-service quality contributes the most in the formation of EWOM, while the dimension of E-service quality that contributes the least in forming EWOM is the customization dimension.